Human, social, and organizational aspects of health information systems - Kushniruk, Andre W., 1958-; Borycki, Elizabeth, 1968-; IGI eBooks; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2008)
"This book offers an evidence-based management approach to issues associated with the human and social aspects of designing, developing, implementing, and maintaining health information systems across a healthcare organization--specific to an individual, team, organizational, system, and international perspective. Integrating knowledge from multiple levels, will benefit scholars and practitioners from the medical information, health service management, information technology arenas"--Provided by publisher.
Health Information Technology Economic Evaluation / Eric L. Eisenstein ... [et al.] -- Legal Issues in Health Information and Electronic Health Records / Nola Ries -- Accountability, Beneficence, and Self Determination: Can Health Information Systems Make Organizations "Nicer"? / Tina Saryeddine -- Electronic Health Records: Why Does Ethics Count? / Eike-Henner W. Kluge -- Technology Enabled Knowledge Translation: Using Information and Communications Technologies to Accelerate Evidence Based Health Practices / Kendall Ho -- Knowledge Translation in Nursing Through Decision Support at the Point of Care / Diane Doran, Tammie Di Pietro -- Improving Internet-Based Health Knowledge Through Attention to Literacy / Jose F. Arocha, Laurie Hoffman-Goetz.
Includes bibliographical references (p. 347-384) and index.
Also available in print.
Mode of access: World Wide Web.
Title from PDF t.p. (viewed on June 22, 2010).
Keywords: Information storage and retrieval systems -- Health services administration; Health services administration -- Data processing; Management information systems -- Human factors; Management information systems -- Social aspects; Management information systems -- Management; Medical Informatics Applications; Health Services Administration; Accountability in healthcare organizations; Best practices; Computer-supported clinical activity; Decision making; Decision support; Economics of healthcare information technology; Electronic health records; Evaluation methods; Evidence-based healthcare practices; Health information systems development; Health information systems management; Health service management; Healthcare information systems; Human roles in IT projects; Internet-based health knowledge; Knowledge translation in healthcare; Legal, ethical, and professional issues; Medical informatics; Organizational methods; Pervasive healthcare; Portable usability testing; Regional patient safety initiatives; Social aspects; Systems implementation; Technology-induced errors in healthcare; Usability methods; Virtual usability laboratories; Electronic books